Normalization of mediastinal widening after successful treatment of mediastinal tuberculosis. Issue 4 (3rd July 2016) - Raskin, Jo; Van Bleyenbergh, Pascal
Abstract : Clinical image of an asymmetrical mediastinal widening due to tuberculosis of mediastinal lymph nodes, without evidence of pulmonary tuberculosis. Image at first presentation and after successful treatment, showing normalization of the mediastinum.